2011
DOI: 10.5539/ass.v7n3p54
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Influential Factors in International Tourism Income in Sichuan Province

Abstract: Sichuan Province is abundant in tourism resources, a big tourism province. Its tourism income occupies a relatively great rate in the total output value of local area. However, an analysis of the tourism income structure of Sichuan Province, it is found that whether in terms of the total output or the proportion it occupies, the international tourism income lags behind domestic tourism income. In the meanwhile, whether compared with such cosmopolis as Beijing and Shanghai or compared with Jiangsu and Shandong,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The results also showed that the number of starred hotels positively augments tourists spending. It also provided empirical support to Yang's [2011] earlier works indicating that the local economy (China's Sichuan Province) is strongly influenced by the competitiveness of its tourism. In addition, we found that an increment in the exchange rate index (using appreciation of the sterling pound versus the euro) matters and tourist spending positively responds to a weakening currency.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The results also showed that the number of starred hotels positively augments tourists spending. It also provided empirical support to Yang's [2011] earlier works indicating that the local economy (China's Sichuan Province) is strongly influenced by the competitiveness of its tourism. In addition, we found that an increment in the exchange rate index (using appreciation of the sterling pound versus the euro) matters and tourist spending positively responds to a weakening currency.…”
Section: Resultssupporting
confidence: 70%
“…Development of the tourism industry is heavily affected by many competitive factors either from a national or global perspective. A study of China's Sichuan Province [Yang, 2011] showed that the local economy is strongly influenced by the competitiveness of the tourism industry (i.e. wage of employees, star hotels, GDP per capita, number of tourists).…”
Section: Competitiveness In the Tourism Industrymentioning
confidence: 99%
“…There are many indicators used to represent human resources for tourism of a locality. Research by Yang et al (2011) uses the number of employees in the tourism industry as an independent variable in their model.…”
Section: Hypothesis Testing and Discussionmentioning
confidence: 99%
“…Natural landscape: Natural landscape is an essential tourism resource. Researches by Yang et al (2011), Ngoc and Trinh (2015) showed that natural landscape has a positive impact on the attractiveness of tourist destinations. The more beautiful and attractive the natural landscape is, the more visitors desire to explore and experience.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%